2012
DOI: 10.1021/ar300053p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rotors: What Lies Behind the High Sensitivity of the Thioflavin-T Fluorescent Marker

Abstract: Thioflavin-T (ThT) can bind to amyloid fibrils and is frequently used as a fluorescent marker for in vitro biomedical assays of the potency of inhibitors for amyloid-related diseases, such as Alzheimer's disease, Parkinson's disease, and amyloidosis. Upon binding to amyloid fibrils, the steady-state (time-integrated) emission intensity of ThT increases by orders of magnitude. The simplicity of this type of measurement has made ThT a common fluorescent marker in biomedical research over the last 50 years. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
369
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(384 citation statements)
references
References 57 publications
15
369
0
Order By: Relevance
“…This is Equation 23. This can be used in conjuction with the timescale formula Equation 1 to yield a timescale for rotation of one of the rotors in a monomethine.…”
Section: Discussionmentioning
confidence: 99%
“…This is Equation 23. This can be used in conjuction with the timescale formula Equation 1 to yield a timescale for rotation of one of the rotors in a monomethine.…”
Section: Discussionmentioning
confidence: 99%
“…[57,58] A very classic assay relies on the use of Thioflavin-T (ThT), a dye that shows a characteristic redshift in the excitation spectrum and strong enhancement of the fluorescence quantum yield upon binding to fibrillary structures. [59][60][61][62] Amyloid fibrils are characterized by laminated -sheets, the strands of which run perpendicular to the long axis of the fibril. [59,62,63] This amyloid composition produces the characteristic reflections (ca.…”
Section: Aggregationmentioning
confidence: 99%
“…[43] Secondly, aggregation protocols to reproducibly promote the formation of these A aggregates are well-established and the resulting aggregates have been extensively characterized using structural imaging methods including atomic-force microscopy (AFM) and electron-microscopy (EM). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] In a previous study we have already shown using EM that the presence of the HiLyte Fluor 555 dye at the N-terminus of the A(1-42) peptide (A 555 ) does not affect the aggregation kinetics or the morphology of the aggregates. [34] Indeed, we observed amyloid structures of A 555 with diameters of ~ 4 nm (fibrils) and ~ 22 nm (globules) which are identical to those obtained in the absence of N-terminal functionalization.…”
Section: Monitoring Amyloid Aggregation and Inhibition Using Fluorescmentioning
confidence: 99%